Clinical evaluation of wheezy chest in children below 2 years of age in Hawler governorate - Ahmed, Parween N.; Chalabi, Dlair AbdulKhalik; Hamad Zangana, Kawes O. (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: Acute respiratory tract infection is a leading cause of childhood morbidity & mortality in developing countries .respiratory distress with wheezing in infants is quite common & presents substantial diagnostic problems. The aim is to determine the clinical characteristics of wheezy chest in children below 2 years of age in Raparin pediatric hospital in Hawler Governorate Methods: a prospective study conducted between 1st of January till 1st of June 2007 in Raparin hospital , three hundreds children of 1-24 months old admitted with respiratory distress & acute wheezing were recruited & 62 children with no respiratory distress were also studied as control cases. Chest x-ray, total & differential WBC counts were undertaken for all of them. Results: of the 300 cases, 191 were due to bronchiolitis. thier age were between 1-6 months (47.23 %), male was the most common gender affected (67.67%).Fever with temperature above 37.7 Cᵒ indicate pneumonia (68.9%) more likely rather than other 2 diseases (asthma ,bronchiloitis). One hundred percent of cases of asthma had history of previous attack of wheeze & +ve family history of atopy.Among bronchopneumonia patients, 77% had opacity in chest x-ray (CXR) while 39.9% of bronchiolitis cases had normal CXR. In 84.8 % of cases with bronchiolitis WBC count were normal with only 4.2% had lymphocytosis, while 11.5% of bronchopneumonia patients had leukocytosis with 24.6% of these cases had neutrophilia. Conclusion: It can be concluded from this study that bronchiolitis, bronchopneumonia & asthma can be differentiated up to reasonable extent on the basis of clinical features supported by simple available investigations..